THE IMPACT OF BRAND EQUITY, PRODUCT QUALITY, AND PRODUCT INNOVATION IN EFFORTS TO ENHANCE PURCHASE DECISIONS FOR MAKITA MAKTEC PRODUCTS AT PT. YANMARINDO PERKASA - Muhammad Wan Kudri; Suyono Suyono; Novita Yulia Putri; Nyoto Nyoto; Yvonne Augustin S; Muhammad Ridwan (Procuratio : Jurnal Ilmiah Manajemen, 2024)
The purpose of this study is to determine the influence of brand equity, product quality and product innovation on the purchase decision of Makita Maktec products at PT. Yanmarindo Perkasa. The data analysis technique of this study uses descriptive analysis and multiple linear regression analysis. The research population is consumers who make purchase transactions at PT. Yanmarindo Perkasa. The sampling technique was used by the Roscoe method. The number of samples in this study is 100 respondents from all customers who have purchased Makita Maktec products at PT. Yanmarindo Perkasa. The data analysis technique used for the SPSS test. The results of this study show that brand equity has a positive and significant effect on purchase decisions while product quality and product innovation have no effect and are not significant on purchase decisions. For researchers interested in conducting further research, it is better to add other variables. Further research can also be conducted on different companies with a wider scope and a larger sample. Tujuan dari penelitian ini adalah untuk menentukan pengaruh dari brand equity, kualitas produk, dan inovasi produk terhadap keputusan pembelian pada produk Makita Maktec di PT. Yanmarindo Perkasa. Teknik analisis data yang digunakan pada penelitian ini adalah analisa deskriptif dan regresi linear berganda. Populasi pada penelitian ini mencakup semua pelanggan yang melakukan transaksi pembelian di PT. Yanmarindo Perkasa. Teknik pengambilan sampel yang digunakan adalah Metode Roscoe dengan jumlah sampel sebanyak 100 responden dari seluruh pelanggan yang pernah membeli produk Makita Maktec di PT. Yanmarindo Perkasa. Teknik analisis data pada penelitian ini menggunakan Uji SPSS. Hasil penelitian menunjukkan bahwa brand equity memiliki pengaruh signifikan positif terhadap keputusan pembelian, sedangkan kualitas produk dan inovasi produk tidak berpengaruh signifikan pada keputusan pembelian. Untuk peneliti selanjutnya, disarankan untuk dapat menambahkan variabel lainnya ataupun melakukan penelitian pada perusahaan lain dengan cakupan dan jumlah sampel yang lebih luas.